Cost- effectiveness of HPV vaccination regime: comparing twice versus thrice vaccinations dose regime among adolescent girls in Malaysia - Syed Aljunid; Nimetcan Mehmet Orhun; Amrizal M Nur; Mohd Rushdan Md Noor; Sharifa Ezat Wan Puteh (BMC, 2016)
Abstract Background The HPV vaccine was introduced to Malaysian national immunization programme in 2010. The current implementation age of HPV vaccination in Malaysian is at the age of 13 years school girls, given according to a 3 doses protocol which may complicate implementation and compliance. Aim of the study is to determine the cost-effectiveness of HPV vaccination regime comparing twice versus thrice HPV vaccinations dose regime among adolescent girls in Malaysia. Methods A Markov cohort model reflecting the natural history of HPV infection accounting for oncogenic and low-risk HPV was adapted for 13 year old Malaysian girls cohort (n = 274,050). Transition probabilities, utilities values, epidemiological and cost data were sourced from published literature and local data. Vaccine effectiveness was based on overall efficacy reported from 3-doses clinical trials, with the assumption that the 2-doses is non-inferior to the 3-doses allowing overall efficacy to be inferred from the 3-doses immunogenicity data. Price parity and life-long protection were assumed. The payer perspective was adopted, with appropriate discounting for costs (3 %) and outcomes (3 %). One way sensitivity analysis was conducted. The sensitivity analysis on cost of vaccine, vaccine coverage and discount rate with a 2-doses protocol was performed. Result The 3-doses and 2-doses regimes showed same number of Cervical Cancers averted (361 cases); QALYs saved at 7,732,266. However, the lifetime protection under the 2-doses regime, showed a significant cost-savings of RM 36, 722,700 compared to the 3-doses scheme. The MOH Malaysia could vaccinate 137,025 more girls in this country using saving 2-doses regime vaccination programme. The model predicted that 2-doses HPV vaccination schemes can avoid additional 180 Cervical Cancers and 63 deaths compare to 3-doses. Conclusion A 2-doses HPV vaccination scheme may enable Malaysian women to be protected at a lower cost than that achievable under a 3-doses scheme, while avoiding the same number of Cervical Cancer cases and deaths. Using the saving money with 2-doses, more Cervical Cancers and deaths can be avoided.